Keefektifan Penggunaan Media Gambar Berseri dalam Keterampilan Menulis Kalimat Sederhana Bahasa Jerman Siswa - Yatri Gilli; Ambo Dalle (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
The purpose of this study was to obtain data related the effectiveness of serial image media in increasing students' simple German sentence writing skills. The design of this study is true Experimental Design (Pretest-Postest Control Group Design). Samples are selected randomly. Data were analyzed using t-test. The results of the analysis show that t-count 5.52 > t table 2.005 at a significant level of 0.05. The results showed that serial image media were effective in increasing students' simple German sentence writing skills.